Sedimentology and paleoenvironments of the Las Chacritas carbonate paleolake, Cañadón Asfalto Formation (Jurassic), Patagonia, Argentina - Cabaleri, Nora Graciela (2013)
The Las Chacritas Member is the lower part of the Cañadón Asfalto Formation (Jurassic). The unit is a completely continental limestone succession with volcanic contributions that were deposited during the development of the Cañadón Asfalto Rift Basin (Chubut province, Patagonia, Argentina). A detailed sedimentological analysis was performed in the Fossati depocenter to determine the paleoenvironments that developed in the context of this rift. The Las Chacritas Member represents a carbonate paleolake system with ramp-shaped margins associated with wetlands that were eventually affected by subaerial exposure and pedogenesis. This process is represented by three main subenvironments: a) a lacustrine setting sensu stricto (lacustrine limestone facies association), represented by Mudstones/. Wackestones containing porifera spicules (F1), Intraclastic packstones (F6) and Tabular stromatolites (F10) in which deposition and diagenesis were entirely subaqueous; b) a palustrine setting (palustrine limestone facies association) containing Microbial Mudstones (F2), Intraclastic sandy packstone with ostracode remains (F3), Oncolitic packstone (F5), Brecciated limestone (F7) and Nodular- Mottled limestone (F8) representing shallow marginal areas affected by groundwater fluctuations and minor subaerial exposure; and c) a pedogenic paleoenvironment (pedogenic limestone facies association) including Intraclastic limestone (F4) and Packstones containing Microcodium (F9) facies displaying the major features of subaerial exposure, pedogenic diagenesis and the development of paleosols. The fluvial-palustrine-lacustrine succession shows a general shallow upward trend in which contraction-expansion cycles are represented (delimited by exposure and surface erosion). The variations in the successive formations reflect the responses to fluctuations in a combination of two major controls, the tectonic and local climatic variables. The predominance of the palustrine facies associations was determined by its accommodation space as well as the local climate conditions. The variations in the lacustrine limestone facies associations reflect differential patterns of subsidence within the sub-basin. The diagnostic features of the palustrine limestone facies associations (organic matter (OM) content, microinvertebrate fauna, abundant mud cracks, brecciation, presence of evaporitic minerals) frame the sub-basin in a climatic context intermediate between arid and subhumid conditions.